Alfred Sohn-Rethel en Italie – question de contexte - Charles Alunni (Recherches Germaniques)
In October 1977, Alfred Sohn-Rethel made his entrance onto the scene of Italian Marxian studies. This was the beginning of an essential and epoch-making companionship between major Italian thinkers and his own philosophical enterprise. 1977 was also the year in which the Italian best-seller, L’Ape e l’architetto, was published in French, under the title L’Araignée et le tisserand (The Spider and the Weaver). The purpose of this article is to resituate Sohn-Rethel’s work within the framework of the critical re-readings of Marxian texts initiated by the work of Raniero Panzieri, and which transversally involved both the “young” Lukács and the partial re-interpretations of Lucio Colletti.